Analysis Policy Scheme Study and Devotion to The Community in Unnes as PTN BH - Utami, Evita Septiana Tyas; Setyaningsih, Wahyu; Sulaksmi, Galih Niken Anggoro (Jurnal Abdimas, 2023)
This research aims to determine the role, efforts and obstacles experienced by savings and loan cooperatives (KSP) in helping the development of Micro, Small and Medium Enterprises (MSMEs) in Karanganyar Regency. The type of research used is qualitative descriptive research. The data collection techniques used were observation, interviews and documentation. The number of research informants was 8 people consisting of 2 employees of the Savings and Loans Cooperative in Karanganyar Regency and 5 micro, small and medium business entrepreneurs. The results of this research are 1) savings and loan cooperatives have a role in the development of micro, small and medium enterprises, such as providing business capital, assisting in economic growth, and playing a role in improving the entrepreneurial spirit of cooperative members. 2) The efforts made by savings and loan cooperatives to help the development of micro, small and medium businesses is by providing business development. 3) Obstacles faced by savings and loan cooperatives in helping the development of micro, small and medium enterprises include the low amount of credit given and the occurrence of installment delays for members.